Radiotherapy in treatment of isolated lymphoma of bones - a cases report - O’Shea, Agnieszka; Skowronek, Janusz (Contemporary Oncology/Współczesna Onkologia, 2002)
Purpose: Chemotherapy is a treatment of choice in a group of lymphomas. Radiotherapy is used in selected cases in treatment of isolated low malignant lymphomas and as a consolidating treatment. Location in bones can be a symptom of disseminated disease or an isolated single location. Due to small group of described cases there are no treatment standards. Because of histological type radiotherapy are often connected successfully with chemotherapy. In this paper we present our results of treatment of isolated lymphoma of bones. Material and methods: Eleven patients with isolated lymphoma of bones underwent radiotherapy between 1993 and 1999 in Greatpoland Cancer Center. There were 8men and 3 women in age between 19 and 72 years. Most frequent location of lymphoma was vertebral column with sacral bone (7 patients) and in single cases: femoral bone, pelvic bone, humeral bone and scapula. In 10 cases radiotherapy was connected with chemotherapy, in 5 cases with surgical removal of lesion located in vertebral column. Total dose reached 20 to 48 Gy, respectively, most frequent 40 Gy (in 5patients), fraction dose ranged from 1,8 Gy to 5 Gy. External beam radiotherapy was performed using gamma - ray irradiation (Co-60 unit, Theratron) or using 6 MV photons. Clinical target volume included tumor or tumor site with adjacent area, most frequent 2-3 cm. Achieved remission was compared with histological type, tumor location and method of treatment. Results: Complete remission (CR) confirmed with radiological and clinical investigations was observed in 3 cases, in 6 cases we observed partial remission, in 2 cases lack of remission. CR was obtained in patients with tumor location in scapula, vertebral bones L2-L3 and humeral bone. In patients with tumor localised in pelvic bone and femoral bone we observed no remission. Three patients survived over 5 years, four patients with recurrence during observation are efficiently treated with chemotherapy. Because of small group of patients and different, no randomly choosen, methods of treatments we didn't analysed influence of dose value on survival rate. Conclusions: 1) Radiotherapy of isolated lymphoma of bones was an effective treatment. Radiotherapy was well tolerated, we didn't observe any complications. 2) Small group of patients makes comparison of different treatment schema impossible, so we can't compare doses of irradiation and results of radiotherapy with group treated exclusively with chemotherapy.